Β1 integrins mediate resistance to ionizing radiation in vivo by inhibiting c‐Jun amino terminal kinase 112. Issue 7 (21st March 2013) - Goel, Hira Lal; Sayeed, Aejaz; Breen, Michael; Zarif, Matthew J.; Garlick, David S.; Leav, Irwin; Davis, Roger J.; FitzGerald, Thomas J.; Morrione, Andrea; Hsieh, Chung‐Cheng; Liu, Qin; Dicker, Adam P.; et al.
Abstract This study was carried out to dissect the mechanism by which β1 integrins promote resistance to radiation. For this purpose, we conditionally ablated β1 integrins in the prostatic epithelium of transgenic adenocarcinoma of mouse prostate (TRAMP) mice. The ability of β1 to promote resistance to radiation was also analyzed by using an inhibitory antibody to β1, AIIB2, in a xenograft model. The role of β1 integrins and of a β1 downstream target, c‐Jun amino‐terminal kinase 1 (JNK1), in regulating radiation‐induced apoptosis in vivo and in vitro was studied. We show that β1 integrins promote prostate cancer (PrCa) progression and resistance to radiation in vivo. Mechanistically, β1 integrins are shown here to suppress activation of JNK1 and, consequently apoptosis, in response to irradiation. Downregulation of JNK1 is necessary to preserve the effect of β1 on resistance to radiation in vitro and in vivo. Finally, given the established crosstalk between β1 integrins and type1 insulin‐like growth factor receptor (IGF‐IR), we analyzed the ability of IGF‐IR to modulate β1 integrin levels. We report that IGF‐IR regulates the expression of β1 integrins, which in turn confer resistance to radiation in PrCa cells. In conclusion, this study demonstrates that β1 integrins mediate resistance to ionizing radiation through inhibition of JNK1 activation. J. Cell. Physiol. 228: 1601–1609, 2013. © 2013 Wiley Periodicals, Inc.